EFFECT OF 90 DECIBEL NOISE OF 4000 HERTZ ON BLOOD PRESSURE IN YOUNG ADULTS - Mahmood, Rashid; Khan, Ghulam Jillani; Alam, Shamim; Safi, Abdul Jalal; uddin, Salah; Haq, Amin -ul- (Journal of Ayub Medical College Abbottabad, 2004)
Background: Almost every individual dislikes excessive and unnecessary noise. Noise exerts various adverse psychological and physiological effects, on human body including a rise in blood pressure. Methods: 117 volunteer medical students, aged 18-23 years were exposed to 90 decibel noise of 4000 hertz for 10 minutes, produced by audiometer in a sound-proof room. Blood pressure was recorded every three minutes. Results: Blood pressure increased during exposure to noise. Average rise in systolic blood pressure was 2.462±0.532 mm Hg and average rise in diastolic blood pressure was 3.064± 1.047mm Hg. Blood pressure came to resting value within two minutes after stopping exposure to noise in more than 50% of the subjects. Conclusion: Systolic and diastolic blood pressure increases due to noise exposure. Key Words: Noise, Blood pressure, Health